1995
DOI: 10.2118/26092-pa
|View full text |Cite
|
Sign up to set email alerts
|

Water/Oil Relative Permeability Endpoints of Intermediate-Wet, Low-Permeability Rocks

Abstract: The relative permeability endpoints oflow-permeability, intermediate-wet mudstones increased with flow rate. This was because of both a decrease in capillary end effect and an increase in capillary number. Hence, conventional analysis will incorrectly describe field behavior. We recommend an improved methodology.We imaged steady-state saturation profiles at the end of different rate floods on one sample. We analyzed these profiles, which were axially nonuniform, to obtain capillary-end-effect-corrected data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…The centrifuging method cannot be gained from the production data at low mobility ratio as it cannot provide information of coal permeability in the low saturation region (Hirasaki and Rohan, 1995). Steady-state methods offer disadvantages, especially in the case of low permeability rocks where it is laborious to reach multiple steady states, and capillary forces and capillary end effects are significant (Firoozabadi and Aziz, 1988;Kamath et al, 1993). J.M.…”
Section: Introductionmentioning
confidence: 99%
“…The centrifuging method cannot be gained from the production data at low mobility ratio as it cannot provide information of coal permeability in the low saturation region (Hirasaki and Rohan, 1995). Steady-state methods offer disadvantages, especially in the case of low permeability rocks where it is laborious to reach multiple steady states, and capillary forces and capillary end effects are significant (Firoozabadi and Aziz, 1988;Kamath et al, 1993). J.M.…”
Section: Introductionmentioning
confidence: 99%
“…Steady-state methods require both phases to approach local equilibrium. This requirement results in time-consuming measurements for lowpermeability porous media because it is laborious to reach multiple steady states that are free of capillary-end effects (Firoozabadi and Aziz, 1991;Kamath et al, 1995). Capillary forces have a significant effect on multiphase flow, saturation distribution as a function of time, and recovery history in low-permeability rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Experience has shown that pressure gradients of more than 4500 kPdm (2OOpdft) are needed for conducting laboratory forced displacement experiments (Kamath et al 1995). The reservoir pressure gradient cannot be more than 110 kPdm (5 pdft), in practice, considering reservoir depth and injectivity.…”
Section: Counter-current Versus Co-current Imbibitionmentioning
confidence: 99%